European Union - The Second Founding - Kühnhardt, Ludger (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
The author is presenting a broadly structured study about the first fifty years of European integration, its geopolitical context and academic reflection. His study is based on the two-fold thesis that since a few years, the European Union is going through a process of its Second Founding while simultaneously changing its rationale.